Trabalho doméstico no Brasil contemporâneo: uma análise sob a perspectiva de raça, classe e gênero - Pereira, Rafaela Leandro (2022)
This dissertation seeks to carry out an analysis of the situation of domestic work in contemporary Brazil from a perspective of race, class and gender, focusing on the post-coup period of 2016. Understanding that domestic work in Brazil is historically and socially marked by the work of black women, who mostly occupy this space of devaluation and invisibility of work. With the 2016 coup, neoliberal rationality exacerbates social and political contradictions, essentially in the context of the Covid-19 pandemic, which leads us to question the situation of domestic work in contemporary times from this perspective. We also highlight the trajectory of struggle and resistance of domestic workers, which is fundamental for the conquest of rights and political and collective organization of the category. For this, we used bibliographical and documentary research, with a critical and historical approach, to deal with domestic work from its particularities. In this way, we seek to contribute to studies on the subject at hand, in view of the need to give greater visibility to domestic work subject to oppression and historical exploitation.